Decomposition of the organic matter in two forest ecosystems (Natural Park of Montseny, Spain) - I. Abundance, biomass and distribution of the soil microarthropods (VIE ET MILIEU-LIFE AND ENVIRONMENT, 1998)
This paper represents the first part of a larger work concerning the importance of the oribatid mites in the edaphic trophic chains of two forests (holm-oak and beech woods) under Mediterranean conditions. We offer here the data relating to annual changes of abundance, biomass and vertical distribution of the mesofauna sorted according taxonomic and trophic criteria. The soil was divided into three layers : fresh fallen leaves (L), fermentation layer (F) and organic horizon (S). Rate of leaf imput, dynamics of decomposition, environmental trophic supply, physical structure of the soil and seasonal drought constitute the factors determining the richness and the spatial arrangement of the fauna.

Biomass Equations for Quercus ilex L. in the Montseny Massif, Northeastern Spain (Forestry, 1988)
Biomass estimation equations for individual holm oak (Quercus ilex spp. ilex) were developed using data from 71 sample trees. Diameter alone was a strong predictor of biomass, but better biomass estimates were obtained when height and crown projection radius were added to the model. In addition to total above-ground dry weight, different biomass components were calculated: stem (greater than 5 cm in diameter), branches 1 to 5 cm in diameter, branches less than 1 cm in diameter, and foliage. Grouping the trees according to height (taller or shorter than 7 m) and aspect (north-and south-facing slopes) resulted in significantly different allometric equations for most of the components considered. Improved estimates were achieved in many cases when D50 (diameter at 0.5 m) was used instead of DBH. Comparison of the results with other published equations developed for Q.ilex and other oaks showed differences, probably due to morphological diversity of trees and different DBH class distribution of samples used.
10.1093/forestry/61.2.137